Applicability of Virechana in Kamala: A Literary Review - Chauhan, Vikas; Sharma, Sonam (International Research Journal of Ayurveda & Yoga, 2022)
In present era, everybody is looking towards ayurveda for health care. Panchkarma is one amongthe primary key elements of ancient documental science of life. Medicated purgation, medicated emesis, medicated enema, nasal medication and bloodletting are the five purification proceduresfor removing accumulated toxins and other waste material in the body. As the humors and tissueare related to each other, these discharge procedures affect the tissue indirectly by the strong elimination of the related humors. Virechana is considered as best therapeutic measures for pitta dosa among all five measures of Panchkarma. Virechana karma is one of the important bio purification measures which is indicated for complete elimination of pitta dosa not only in pathological stage but also in physiological stage, as explained under seasonal regimen of autumn season. Kamala is Pittaja Nanatmaja as well as Raktapradoshaja Vyadhi. Charakacharya has considered kamala as advanced stage of Pandu Roga. Sushrutacharya has considered kamala as a separate disease and also may be due to further complication of Panduroga, whereas Vagbhatacharya described kamala as a separate disease. Kamala can be correlated with jaundice in modern medical science. In Kamala Vyadhi acharyas has explained Virechana Karma.